An exploratory study into middle-class parental orientations and values towards their children’s education - Ong, Theresa (2016)
Researches on social class and parenting have a tendency to homogenize middle-class parents’ experiences. Using qualitative interviews, this study seeks to explore middle-class diversity on parental values and strategies to children’s education in Singapore. In particular, this study explores 1) parents’ orientations towards their child’s education, 2) secondary school choice process and dynamics and 3) the meanings attached to these parental orientations. Findings of this study reveal diverse parental orientations and meanings to their children’s education within the middle-class. These differences are linked to the different types of capital – economic, social, cultural – that each middle-class sub group possesses.